2022
DOI: 10.1021/acs.inorgchem.1c03196
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Lα1 High Energy Resolution Fluorescence Detected X-ray Absorption Spectroscopy: A Versatile Speciation Probe for Mercury

Abstract: Mercury is in some sense an enigmatic element. The element and some of its compounds are a natural part of the biogeochemical cycle; while many of these can be deadly poisons at higher levels, environmental levels in the absence of anthropogenic contributions would generally be below the threshold for concern. However, mercury pollution, particularly from burning fossil fuels such as coal, is providing dramatic and increasing emissions into the environment. Because of this, the environmental chemistry and toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…We also examined the possibility of other mercury chemical species, in particular methylmercury l selenocysteinate, which when incorporated into the linear combination fitting schemes did show subtly improved fits in some cases. As we have previously noted, , the Hg Lα1 HERFD-XAS spectra of methylmercury l -selenocysteinate and methylmercury l -cysteinate are very similar, but the features of the Hg Lα1 HERFD-XAS for the selenium congener are shifted slightly to lower energy. , Such coordination might originate through inhibition of essential selenoenzymes. We have recently shown that methylmercury inhibits the essential selenoenzyme thioredoxin reductase through covalent binding of the selenolate of the active site selenocysteine residue .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also examined the possibility of other mercury chemical species, in particular methylmercury l selenocysteinate, which when incorporated into the linear combination fitting schemes did show subtly improved fits in some cases. As we have previously noted, , the Hg Lα1 HERFD-XAS spectra of methylmercury l -selenocysteinate and methylmercury l -cysteinate are very similar, but the features of the Hg Lα1 HERFD-XAS for the selenium congener are shifted slightly to lower energy. , Such coordination might originate through inhibition of essential selenoenzymes. We have recently shown that methylmercury inhibits the essential selenoenzyme thioredoxin reductase through covalent binding of the selenolate of the active site selenocysteine residue .…”
Section: Resultsmentioning
confidence: 99%
“…As we have previously noted, 14,30 the Hg Lα1 HERFD-XAS spectra of methylmercury L-selenocysteinate and methylmercury Lcysteinate are very similar, but the features of the Hg Lα1 HERFD-XAS for the selenium congener are shifted slightly to lower energy. 27,30 Such coordination might originate through inhibition of essential selenoenzymes. We have recently shown that methylmercury inhibits the essential selenoenzyme thioredoxin reductase through covalent binding of the selenolate of the active site selenocysteine residue.…”
Section: Acs Chemical Neurosciencementioning
confidence: 97%
See 2 more Smart Citations
“…In 1991, Hämälainen et al demonstrated the dramatic sharpening of HERFD XAS technique on the L 3 edge of dysprosium, laying the foundation for the increasingly popular HERFD XAS approach. Today, the technique is being widely applied across the periodic table for a variety of elements, including the first, , second, and third row transition metals, main group elements, halogens, lanthanides, and actinides. …”
Section: X-ray Spectroscopic Methods and Recent Applicationsmentioning
confidence: 99%